THE ROLE OF WOMEN AS MEMBERS OF THE UNITED NATIONS SECURITY FORCES (Indonesian Women's Security Forces Recruitment Process) - Fenny Wulandari; Abdul Azis (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2019)
International organizations are formed by an agreement in which three or more countries are parties, or also called intergovernmental organizations because their members are state. The state as a party to the international organization must accept the obligations arising from the agreement. Countries incorporated in an international organization usually have the same interests and goals. Even in some difficulties and to help progress the member countries of the international organization did not hesitate to provide assistance. International organizations such as the United Nations have the aim of maintaining international peace and security. The establishment of the United Nations (UN) was set against the concerns of mankind for international peace and security based on the experience of the First World War and the Second World War. Indonesia's commitment to participate in carrying out world order based on independence, lasting peace and social justice is the mandate of paragraph IV of the Opening of the 1945 Constitution of the Republic of Indonesia. This commitment is always realized through Indonesia's active participation and contribution in the UN Mission of Maintenance and Peace. In the international context, participation is an important and concrete indicator of the role of a country in contributing to maintaining international peace and security.